MELESTARIKAN KEARIFAN ETNOBOTANI MELALUI KENDURI SKO DUA LUHAH PENDUNG: PENDIDIKAN DAN PEMETAAN TUMBUHAN - Tomi Apra santosa; Nahria, Nahria; Toni Haryanto; Indah Kencanawati (PUAN INDONESIA, 2025)
Kenduri Sko is one of the sacred traditional traditions of the people of Dua Luhah Pendung, Kerinci Regency, which is rich in cultural values and local knowledge, especially in the use of traditional plants. The ethnobotanical knowledge inherent in this ritual reflects local wisdom that has been passed down from generation to generation, but now faces challenges due to modernization and diminished interest of the younger generation. This community service activity aims to preserve ethnobotanical knowledge through participatory education and mapping of traditional plants used in Kenduri Sko. The methods used include interviews with indigenous and community leaders, documentation of plant types, and educational training for local youth and students. The results of the activity showed an increase in public awareness of the importance of local plant conservation as well as the formation of digital maps and simple catalogs of plants that play a role in traditional ceremonies. This program is expected to be the first step in maintaining the sustainability of local culture and biological resources as part of the ecological and social identity of the Kerinci people.